Efektivitas Gabungan Biji Asam Jawa dan Biji Alpukat sebagai Biokoagulan dalam Menurunkan Parameter Limbah Cair Tahu - Assha, Siva Hiyaul; Adzillah, Wilma Nurrul; Amanah, Nadia (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Tofu wastewater contains high levels of organic pollutants, which has the potential to pollute the environment, which has an impact on decreasing water quality, triggering unpleasant odors, and potentially causing health problems. Coagulation-flocculation is a common method to reduce pollution because it is effective in reducing COD and TSS. However, synthetic coagulants have a negative impact on the environment, produce excess sludge, and require high costs. Tamarind seeds and avocado seeds contain protein and tannins that act as natural polyelectrolytes to reduce organic matter and suspended solids. This study aims to identify the COD, TSS, and pH content of tofu wastewater and analyze the effectiveness of the combination of the two seeds as biocoagulants using the jar test method with dose variations. There are 8 variations in biocoagulant doses, each as much as 4 g/L with different dose ratios, namely control, 100:0, 0:100, 70:30, 60:40, 50:50, 40:60, and 30:70. The results showed that the combination of the two biocoagulants was able to significantly reduce COD and TSS concentrations with the highest reduction effectiveness of 69% and 88%, respectively. The best dose for reducing COD was dose C, while for TSS was dose E. Thus, tamarind seeds and avocado seeds have the potential as an alternative environmentally friendly coagulant in industrial wastewater treatment.